Oral gauze for bleeding control in perioral and perinasal dermatologic surgery - Riyad N H Seervai; Jose A Cervantes; Ikue Shimizu; Ida F Orengo (Wolters Kluwer Medknow Publications, 2023)
The use of oral gauze is a quick, cheap, and effective method of preventing bleeding into the patient's mouth during dermatologic surgery. We recommend this technique combined with appropriate positioning for lesions in the perioral and perinasal regions. Similar approaches may be applied for the prevention of bleeding into the ear canal during facial/periauricular surgery.